Motives for Paying Taxes among Recipients of Article 21 Income Tax Borne by the Government - Ismail Khozen; Milla Sepliana Setyowati (Politeknik Negeri Bengkalis, 2022)
The emergence of Covid-19 cases over the past few years has altered the previously established socioeconomic structure. The government must keep a close eye on changes in the culture of tax compliance, as tax revenues are the keystone of the government's ability to carry out its functions. Because the government finances many social and health initiatives during the pandemic through the contribution of tax revenues, it is pertinent to examine the motivation to pay taxes among recipients of the Article 21 Income Tax borne by the government. Using quantitative descriptive statistics, this study examines intrinsic motivation, perceptions of the worthinessÂ of public expenditures, and tax fairness in the context of the Jakarta region, Indonesia. In addition to providing the motives for paying taxes, this study emphasizes the significance of the efficiency of government expenditures.